Motivational determinants in the process of learning English as a foreign language - Turayeva, Khurshida (The Lingua Spectrum, 2025)
This article examines the pivotal role of motivation in learning English as a Foreign Language (EFL). It establishes motivation as the key driving force behind a learner’s effort, strategy use, and persistence. The text outlines foundational theoretical frameworks, including integrative/instrumental and intrinsic/extrinsic motivation. It then analyzes crucial determinants affecting motivation, such as the teacher’s role, learning environment, cultural context, and learners’ self-efficacy. Moreover, a significant portion is dedicated to practical pedagogical strategies for fostering motivation. These include implementing communicative activities like role-plays and problem-solving tasks, utilizing technology and project-based learning, providing constructive feedback, and promoting learner autonomy. It emphasizes that connecting language learning to real-world contexts and cultural interaction is essential for developing meaningful, integrative motivation. As well as, the article concludes that understanding and nurturing these motivational factors is critical for creating effective learning environments that lead to sustained linguistic competence and a positive attitude toward lifelong learning.